Strategic Cyber Public Relations: A Case Study of PT PLN Nusantara Power’s Engagement on Instagram - Teguh, Monika; Dafa, Muhammad; Aji, Imanuel Deny Krisna; Sistiawan, Ivana Clairine (CHANNEL: Jurnal Komunikasi, 2023)
In the wake of the COVID-19 pandemic, digital communication channels, particularly social media platforms, have become pivotal for organizations worldwide. This study presents a detailed analysis of PT PLN Nusantara Power’s (PT PLN NP) strategic Cyber Public Relations (PR) activities on Instagram. PT PLN NP, a leading energy company in Indonesia, adeptly navigated the digital landscape, earning recognition as the "Most Popular BUMN Subsidiary in Digital Media." Through a comprehensive exploration of PT PLN NP’s cyber PR strategies, encompassing planning, implementation, and evaluation stages, this research provides valuable insights into effective online engagement. The study delves into the contextualization of content, emphasizing its alignment with both internal company dynamics and public interests. It highlights the importance of communication strategies, focusing on the creation of valuable, engaging content tailored to audience needs. Collaborative initiatives, involving partnerships with external entities, are examined as essential components fostering brand affinity. Additionally, the study underscores the significance of real-time interaction and connection with the audience, ensuring the company’s responsiveness and fostering a sense of community. This research offers a robust framework for organizations aiming to enhance their cyber PR efforts, emphasizing the importance of Instagram as a strategic communication tool.